THE PROBLEM OF RESPONSIBLE ATTITUDE STUDENTS BEFORE STUDYING (Pedagogy of Higher and Secondary Education, 2022)
The article is discovered content of concept „responsible concern to the studies”, character o f levels its forming is defined, its initial level and causes o f low level of the forming at students of the pedagogical university is defined too.